Understanding Parents' Experiences When Caring for a Child With Functional Constipation: Interpretive Description Study - Thompson, Alison P; MacDonald, Shannon E; Wine, Eytan; Scott, Shannon D (JMIR Publications, 2021)
BackgroundPediatric functional constipation (FC) is a common but serious medical condition. Despite significant effects on children, families, and the health care system, the condition is typically undertreated. Parents carry the primary responsibility for complex treatment programs; therefore, understanding their experiences and needs may offer a critical perspective toward improving clinical care. ObjectiveThe aim of this study is to understand and give voice to parents' experiences and information needs when caring for a child with FC. The ultimate objective is to build an evidence base suitable for creating a digital knowledge translation tool to better support parents caring for a child with FC. MethodsThis qualitative design used an interpretive description methodology to generate findings aimed at improving clinical care. One-on-one, in-depth interviews were completed either in person or through web-based teleconferencing to explore parents' perspectives. Data collection and analysis occurred concurrently. ResultsAnalysis of 16 interviews generated 4 major themes: living in the shadows; not taken seriously, with a subtheme of persevering and advocating; missing information and misinformation; and self-doubt and strained relationships. One minor theme of affirmative influences that foster resilience and hope was identified. ConclusionsParents have unmet needs for support and information related to pediatric FC. To address gaps in current care provision, decision makers may consider interventions for clinicians, resources for parents, and shifting care models to better meet parents' needs.